2010
DOI: 10.1186/1477-7819-8-64
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor status predicts response to chemotherapy, not risk of breast cancer in Indian women

Abstract: BackgroundConsiderably little is known about the biological role and clinical significance of androgen receptor expression in breast cancer. The objectives of this study were to characterize AR-CAG repeat genotypes in a cohort of women with breast cancer and to determine the influence of AR on response to neoadjuvant chemotherapy and clinical outcome.Materials and methodsGenotyping of the AR CAG repeat region was done on 70 patients and 80 healthy aged- matched female controls. To assess response to NACT, tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…In cohorts not selected on the basis of estrogen receptor-a (ERa (ESR1)) status, AR positivity has been associated with longer relapse-free, metastasis-free and overall survival, smaller tumour size and lower histological grade (Bryan et al 1984, Langer et al 1990, Kuenen-Boumeester et al 1992, Soreide et al 1992, Schippinger et al 2006, Agrawal et al 2008, Gonzalez et al 2008, Hanley et al 2008, Ogawa et al 2008, Soiland et al 2008, Park et al 2010, Yu et al 2011, Peters et al 2012, Honma et al 2013. High AR levels have also been associated with a favourable response to chemotherapy and hormonal therapy, including antioestrogens, aromatase inhibitors and progestins (Teulings et al 1980, Bryan et al 1984, Birrell et al 1995, Agrawal et al 2008, Chintamani et al 2010, Chanplakorn et al 2011, Loibl et al 2011. Importantly, AR has also been shown to be an independent predictor of relapse-free, metastasis-free and/or overall survival in some studies (Soreide et al 1992, Gonzalez et al 2008, Soiland et al 2008, Yu et al 2011.…”
Section: Prognostic Value Of Ar Expression In Breast Cancermentioning
confidence: 99%
“…In cohorts not selected on the basis of estrogen receptor-a (ERa (ESR1)) status, AR positivity has been associated with longer relapse-free, metastasis-free and overall survival, smaller tumour size and lower histological grade (Bryan et al 1984, Langer et al 1990, Kuenen-Boumeester et al 1992, Soreide et al 1992, Schippinger et al 2006, Agrawal et al 2008, Gonzalez et al 2008, Hanley et al 2008, Ogawa et al 2008, Soiland et al 2008, Park et al 2010, Yu et al 2011, Peters et al 2012, Honma et al 2013. High AR levels have also been associated with a favourable response to chemotherapy and hormonal therapy, including antioestrogens, aromatase inhibitors and progestins (Teulings et al 1980, Bryan et al 1984, Birrell et al 1995, Agrawal et al 2008, Chintamani et al 2010, Chanplakorn et al 2011, Loibl et al 2011. Importantly, AR has also been shown to be an independent predictor of relapse-free, metastasis-free and/or overall survival in some studies (Soreide et al 1992, Gonzalez et al 2008, Soiland et al 2008, Yu et al 2011.…”
Section: Prognostic Value Of Ar Expression In Breast Cancermentioning
confidence: 99%
“…Many authors [15][16][17][18][19][20][21][22][23][24][25][26] have found no relationship between the number of CAG repeats in the androgen Table 4. Association of CAG repeat genotypes and alleles in the AR gene with the clinical-pathological parameters of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in mRNA levels of Androgen Recepator (AR) gene related to the chemotherapyinduced apoptosis could serve as an important independent predictor of response to NACT. The AR may thus serve as an important independent predictor of response to NACT and may help in tailoring of the regime for a particular patient.AR appears as a promising predictive biomarker for assessing response to neo-adjuvant chemotherapy in patients with locally advanced breast cancer [25] Immunohistochemical AR expression was evaluated on a tissue microarray of 673 core biopsies from primary breast cancer patients treated with neoadjuvant docetaxel/ doxorubicin/cyclophosphamide (TAC) chemotherapy in the prospective GeparTrio phase-III trial. AR was detected in 53.2 % of tumors while it was detected in 13.33 % tumors in the present study.…”
Section: Discussionmentioning
confidence: 99%